Marketing Study of Beef Cattle Businesses for Sacrificial Animals in the Bekasi Metropolitan Area - Ardisela, Dawud; Budiyono, Haris; Patoni, Sandi Kurniawan (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
This study aims to (1) identify internal factors, which include strengths and weaknesses in the marketing aspects run by CV Berkah Bersama Sejahtera company; (2) Identify external factors, which include threats and opportunities in the marketing aspect carried out by the CV Berkah Bersama Sejahtera company; and (3) Formulating a relevant and effective marketing strategy for CV Berkah Bersama Sejahtera. The method used in this research is a case or field research method. Information and data related to the internal and external environment evaluation are processed using SWOT analysis to determine which strategy is chosen, and then QSPM analysis is used. The results show the mapping of IFE and EFE matrices: directing alternative strategies in the growth and development section. Alternative strategies in the growing section include integration strategies (backwards, forward, and horizontal), and alternative strategies in the building section are intensive strategies are (a) conducting managerial development and independent business development planning efforts to develop feeder cattle cultivation and approaches to local communities in supporting business sustainability and development; (b) utilising the facilitation of government and local government policies, to develop good farming practices (GFP) and capital for business development. The other three strategies based on STAS in QSPM are part of the proposed marketing mix strategy.